Safety and Efficacy of Nanosecond Pulsed Electric Field Treatment of Sebaceous Gland Hyperplasia. Issue 6 (June 2020) - Munavalli, Girish S.; Zelickson, Brian D.; Selim, Mona M.; Kilmer, Suzanne L.; Rohrer, Thomas E.; Newman, James; Jauregui, Lauren; Knape, William A.; Ebbers, Edward; Uecker, Darrin; Nuccitelli, Richard
Abstract : BACKGROUND: Nanosecond pulsed electric field (nsPEF) technology involves delivery of ultrashort pulses of electrical energy and is a nonthermal, drug-free technology that has demonstrated favorable effects on cellular structures of the dermis and epidermis. OBJECTIVE: Determine the tolerability and effectiveness of nsPEF treatment of sebaceous gland hyperplasia (SGH). METHODS: This study was a prospective, randomized, open-label, multisite, nonsignificant risk trial in which each subject served as their own control. After injection of local anesthetic, high-intensity, ultrashort pulses of electrical energy were used to treat 72 subjects resulting in a total of 222 treated lesions. Subjects returned for 3 to 4 follow-up evaluations with photographs. RESULTS: At the final study visit, 99.6% of treated SGH lesions were rated clear or mostly clear and 79.3% of the subjects were satisfied or mostly satisfied with the outcome. At 60 days after nsPEF treatment, 55% of the lesions were judged to have no hyperpigmentation and 31% exhibited mild post-treatment hyperpigmentation. At the last observation for all lesions, 32% of the 222 lesions were noted as having slight volume loss. CONCLUSION: Nanosecond pulsed electric field procedure is well tolerated and is very effective in the removal of SGHs. TRIAL REGISTRATION: ClinicalTrials.gov NCT03612570.